BAP251: Extensive Listening Skills / Academy of Language Studies - UiTM, Academy of Language Studies (2020)
This course aims to guide and sharpen authentic Arabic listening skills among students. They will be trained using several learning activities which involve authentic and spontaneous audio-visual materials. Students will also demonstrate their capability in spontaneous Arabic listening skills through these activities.